Efectos de la extracción de productos forestales no maderables en la conservación del bosque de Tamshiyacu, Fernando Lores, Maynas, Loreto, 2024 - Saavedra Jarama, Christian Martin (2025)
This study was conducted in Tamshiyacu, Fernando Lores District, Maynas Province, Loreto, to evaluate the effects of non-timber forest producto extraction on the conservation of the Tamshiyacu forest. The results show that the majority of respondents etract non-timber forats products regularly (82%). Extraction is primarily comercial in nature (63%). Perceptions of the ecological impact of non timber forest producto extraction vary, with a significant percentage (47%-57%). Non-timber forest producto extraction contributes significantly to community income (49%-63%). Income generated from extraction is primarily used to cover basic needs (54%). The community is willing to receive training on sustainable management (72%). The majority of respondents (65%) beleive that local authorities should become more involved in regulating extraction. There is a high consensus (61%) in the community on the need to implement more sustainable practices for the extraction of non-timber forest products. The null hypothesis, which states that the sustainable extraction of non-timber forest products (NTFPs) does not contribute to the conservation of the Tamshiyacu forest, is rejected. The alternative hypothesis is accepted indicating that there i a relationship between the dependent and independent variables.